VD_FINDINFO Décision / 2012 / 654 vom 21. März 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, SECRET PROFESSIONNEL, AVOCAT, PLAINTE PÉNALE | 321 CP, 13 al. 1 LLCA, 310 CPP (CH), 393 al. 1 let. a CPP (CH)